Vibrational spectroscopic studies and computational study of 4-fluoro-N-(2'-hydroxy-4'-nitrophenyl)phenylacetamide - Mary, YS
Fourier-transform infrared (FT-IR) and FT-Raman spectra of 4-fluoro-N-(2'-hydroxy-4'-nitrophenyl)phenylacetamide were recorded and analyzed. A surface-enhanced Raman scattering (SERS) spectrum was recorded in silver colloid. The vibrational wavenumbers and corresponding vibrational assignments were examined theoretically using quantum mechanical calculations. The red shift of the NH stretching wavenumber in the IR spectrum from the calculated wavenumber indicates the weakening of NH bond resulting in proton transfer to the neighboring oxygen atom. The presence of CH(2) and NO(2) modes in the SERS spectrum indicates the nearness of these groups to the metal surface, which affects the orientation and metal molecule interaction. The presence of phenyl ring deformation bands, show a tilted orientation of the molecule with respect to the silver surface. The first hyperpolarizability and predicted infrared intensities are reported. The calculated first hyperpolarizability is comparable with the reported values of similar structures and is an attractive object for further studies of nonlinear optics. (c) 2011 Elsevier B.V. All rights reserved.